AB0466 The effect of omega-3 fatty acids on disease activity, endothelial function, inflammatory markers, and lipid profile in systemic lupus erythematosus: a systematic review and meta-analysis of randomized, controlled trials. (15th June 2017) - Castillo, R; Uy, PP; Francisco, DM; Lakshminarayanan, S
Abstract : Background: Omega-3 fatty acids have been shown to have potentially beneficial immunomodulatory activity in autoimmune conditions such as rheumatoid arthritis and Sjogren's syndrome. Whether this extends to systemic lupus erythematosus (SLE) remains unclear. Objectives: We undertook this study to summarize the body of evidence available from published clinical trials on the effectiveness of omega-3 fatty acids on clinical and laboratory outcomes in SLE. Methods: Two independent reviewers systematically searched PubMed, MEDLINE, Scopus, and the reference lists of related articles for studies published from inception to November 2016 using relevant keywords. Randomized, controlled trials (RCTs) on SLE patients comparing omega-3 fatty acids with placebo were included in the analysis. The quality of the included RCTs was assessed in accordance with the Cochrane Handbook. A random effects model was used to pool extracted data. Heterogeneity was evaluated with Chi 2 test and I 2, with p -values <0.05 considered significant. Data presented in median and interquartile range were converted to mean and standard deviation using the method described by Wan et al. Results: A total of seven clinical trials consisting of 303 subjects with a duration of treatment ranging from 12 to 52 weeks were included. In studies using SLAM-R as the measurement of disease activity (n=82), there was a statistically significant mean score reduction in the omega-3 fatty acid group vs. the placebo group at 24 weeks. However, in studies that used mean change in SELENA-SLEDAI (n=117, WMD: -0.87, 95% CI: -3.9, 2.17, I 2 =0%, p=0.58) and PGA (n=117, WMD -0.46, 95% CI: -1.16, 0.24, I 2 =85%, p=0.20) scores, there was no significant effect (Figure 1 ). Mean brachial artery diameter after 12 weeks likewise did not reveal any difference between the two groups (n=141, WMD: -0.01, 95% CI: -0.03, 0.01, I 2 =0%, p=0.26). The data on percent increase in flow-mediated dilation was conflicting. In terms of inflammatory markers, there were likewise no clear associations, with some studies reporting significant changes in ESR, CRP, IL-12, and IL-13 levels which were not observed in others. With regards to lipid profile, treatment with omega-3 fatty acids was associated with a non-significant trend toward increase in all lipid profile parameters at 12 weeks including HDL (WMD 6.83, 95% CI: -4.37, 18.02, I 2 =12, p=0.23), LDL (WMD 5.41, 95% CI: -1.27, 12.10, I 2 =0%, p=0.11), and total cholesterol (WMD 8.48, 95% CI: -0.38, 17.33, I 2 =0, p=0.06). Conclusions: The limited data on the use of omega-3 fatty acids has not shown clear benefit in improving disease activity, endothelial function, inflammatory markers, or lipid profile in patients with SLE. Larger studies for longer durations using standardized scales for measuring outcomes are needed. References: Wan X, Wang W, Liu J, Tong T. Estimating the sample mean and standard deviation from the sample size, median, range and/or interquartile range. BMC Med Res Methodol. 2014;14:135–148. Acknowledgements: Dr. Chia-Ling Kuo. Disclosure of Interest: None declared